1995
DOI: 10.1007/bf00202170
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycosides: single or multiple daily dosing?

Abstract: A number of randomised studies indicate that a single high dose of aminoglycoside every 24 h may be more efficient and less toxic than the same dose divided into multiple daily doses. In the meta-analysis of 16 studies described here, which included more than 1200 patients, the relative chance (i.e. the relative risk, RR) of cure of the single-dose regime compared with the multiple-dose regime was 1.027, indicating that the single daily dose regime had a 2.7% higher cure rate (NS). The RR of avoiding nephrotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 14 publications
0
57
0
1
Order By: Relevance
“…[9][10][11][12][13][14][15][16]48 Those meta-analyses showed no difference in clinical efficacy between ODD and MDD 9,13,14,16 or even better efficacy with ODD. [10][11][12]15 With the exception of severely ill children, clinical failures were uncommon in the trials we analyzed, regardless of the regimen used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[9][10][11][12][13][14][15][16]48 Those meta-analyses showed no difference in clinical efficacy between ODD and MDD 9,13,14,16 or even better efficacy with ODD. [10][11][12]15 With the exception of severely ill children, clinical failures were uncommon in the trials we analyzed, regardless of the regimen used.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we observed a trend toward fewer bacteriologic failures, which again was consistent with the results of adult meta-analyses that evaluated this outcome. 10,11,14,15,48 One meta-analysis 9 of adult data suggested that ODD might reduce nephrotoxicity, whereas other meta-analyses [10][11][12][13][14][15]48 showed nonsignificant trends or no difference in nephrotoxicity outcomes. In our meta-analysis, we were not able to show any reduction in the risk of primary nephrotoxicity outcomes with ODD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that pulse dosing minimises toxicity while reducing treatment failure, morbidity and mortality. Pulse dosing or high-peak-extendedinterval dosing of aminoglycosides was first used by Labowitz et al (1974) in man and it has been accepted that there is no significant difference in safety between pulse dosing and multiple-dose regimes (Galloe et al, 1995;Barza et al, 1996;Ferriols-Lisart and Alós-Almiñana, 1996). Furthermore, efficacy is thought to be superior when using pulse dosing of aminoglycosides (Tran Ba Huy and Deffrennes, 1988;Pettarossi et al, 1990;Campbell et al, 1996).…”
mentioning
confidence: 99%